1966
DOI: 10.1021/ic50038a028
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis, Structures, and Solution Equilibria of Bis(pyrrole-2-aldimino)metal(II) Complexes

Abstract: Et -Ed. c ß = KiKiK$ for bipy and K,K% for terpy. d Estimated.12 diethylenetriamine complexes.The corresponding ratio for the zinc and cadmium complexes is only 1.2, Bis (pyrrole-2-aldimino) metal (II) Complexes 625 suggesting that terpyridine chelates comparatively more weakly with these metal ions. It is unlikely, however, that they are acting as bidentate ligands only, since the structure of Zn (terpy) Cl2 shows that all three nitrogens coordinate with only minor strain.13 Although there are puzzling f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

1968
1968
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(54 citation statements)
references
References 1 publication
0
54
0
Order By: Relevance
“…The filtrate was concentrated by evaporating the solvent to dryness. The white solid was washed with diethyl ether (3 X 10 ml) yielding pure Zn2(l) 2 …”
Section: The Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…The filtrate was concentrated by evaporating the solvent to dryness. The white solid was washed with diethyl ether (3 X 10 ml) yielding pure Zn2(l) 2 …”
Section: The Ligandsmentioning
confidence: 99%
“…The complex Zn(pyrrole-2-CH=N-t-Bu)s has already been prepared by Holm and co-workers [2] and some crystallographic data, such as space group (Pbcn) and cell constants have been published [7]. In order to investigate the coordination properties of the pyrrole-2-CH=N-moieties to zinc(I1) in more detail we solved the X-ray structure of complex 3 (see ref.…”
Section: Zn(n'nj2 Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] [18] The difficulties in isolating a complex of the salicylaldimTherefore, whereas salicylaldimines usually lose a proton ine quarter-unit 4 led us to study the condensation reaction upon metal complexation to become uninegative ligands, β-of 1 with 1 equiv. of a related carbonyl substrate, acetylketoamines may be either uninegative or neutral in their acetone (2,4-pentanedione).…”
Section: Resultsmentioning
confidence: 99%
“…complexes, bis-(N-t-butylpyrrole-2-carbaldimino)M(II) (M=Co, Ni, Cu, and Zn) (Holm, Chakravorty & Theriot, 1966;Wei, 1972b), the structural analysis of the nickel complex was previously undertaken from a set of three-dimensional photographic data (Wei, unpublished work). The results showed that the overall structure of the nickel complex was similar (but not isomorphous) to that of the analogous cobalt complex (Wei, 1972a) except that the NiN4 coordination was more distorted so as to be less tetrahedral.…”
Section: Introductionmentioning
confidence: 99%